Asphalt-based lithium ion battery silicon-carbon negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202310842365.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-07-10
AI Technical Summary
然而,目前采用硅作为锂离子电池负极材料仍存在两个关键问题:(1)硅基材料在脱嵌锂离子的过程中有很大的体积变化(~400%),会导致材料发生粉化,电极结构崩塌;(2)硅基材料具有较差的导电性,导致倍率性能差
[0033](1)低共熔溶剂是一种绿色高效的溶剂,具有强溶解能力,成本远低于离子液体。用低共熔溶剂溶解沥青,比其他有机溶剂更稳定、更安全,且能抑制副反应产生的副产品,且低共熔溶剂溶解沥青中的芳香醚和芳香烃等组分,使其更好地包覆硅粉。
Smart Images

Figure BDA0004331093360000091 
Figure BDA0004331093360000101 
Figure HDA0004331093370000011
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery anode technology, specifically relating to an asphalt-based high-capacity integrated silicon-carbon anode for lithium-ion batteries, its preparation method, and its application in lithium-ion batteries, particularly silicon-carbon anode materials. Background Technology
[0002] Graphite, as a traditional anode material for lithium-ion batteries (LIBs), suffers from a theoretically low specific capacity (372 mAh g / g). -1 The narrow interlayer spacing leads to problems such as low ion diffusion coefficient and the formation of lithium dendrites during high-rate charging and discharging, causing safety hazards. This forces us to develop a new type of lithium-ion battery anode material with high energy density, high rate performance, high safety, and easy mass production.
[0003] In recent years, silicon has been extensively studied as a negative electrode material for lithium-ion batteries. This is due to the high theoretical specific capacity of silicon-based materials (4200 mAh g). -1 ), a suitable discharge platform (~0.4V vs. Li / Li) + Silicon has advantages such as preventing lithium dendrite formation and ensuring high operating voltage, abundant reserves, low price, and environmental friendliness, and is expected to become the next generation of new lithium-ion battery anode material. However, there are still two key problems with using silicon as a lithium-ion battery anode material: (1) Silicon-based materials have a large volume change (~400%) during the process of lithium ion insertion and extraction, which will cause the material to pulverize and the electrode structure to collapse; (2) Silicon-based materials have poor conductivity, resulting in poor rate performance.
[0004] To address these two issues, researchers have proposed many methods to improve the lithium storage performance of silicon, which can be mainly divided into the following three directions: (1) Silicon nano-sizing. Nano-sized silicon can solve the problem of pulverization of silicon-based materials. The smaller the particles, the smaller the stress generated by lithium intercalation. When the size is small enough, the stress generated by lithium intercalation is less than the cohesive force of the material itself, and the material will not crack. At the same time, after the silicon material is nano-sized, the migration path of lithium ions in the process of lithium intercalation and deintercalation is shortened, which improves the electrochemical reaction kinetics of silicon-based materials. However, simple nano-sizing will cause the nano-silicon to agglomerate, resulting in severe capacity decay of the battery after long cycles. (2) Designing microporous structures with reserved voids. Designing carbon-coated silicon-based materials with reserved voids can improve the cycle stability of silicon-based anodes. The reserved voids inside this structure can provide space for the expansion of silicon particles, and the static outer carbon shell can ensure the formation of a stable SEI film, while having good electronic and ionic conductivity, improving electrochemical reaction kinetics. However, the methods for reserving void structures are generally more complex, costly, and difficult to industrialize. (3) Improving binders. Silicon-based materials typically have hydroxyl functional groups on their surface, and adhesives that interact with hydroxyl groups can bond them better.
[0005] Most reported preparation processes for silicon-carbon composite materials are quite complex. Typically, silicon is coated with carbon using spray drying and chemical vapor deposition (CVD) to form a core-shell structured silicon-carbon anode material. For example, porous Si-SiOx is prepared by pretreating SiO2 in an inert atmosphere (He) at 950°C. Then, using an Fe-Ni alloy as a catalyst and a CO / H2 / C2H4 mixture as the carbon source, core-shell structured Si / C nanofibers are prepared by CVD as the silicon-carbon anode material. This material achieves a current density of 0.2 Ag... -1 The initial reversible capacity is 1411 mAh g. -1 After 100 cycles, the capacity retention rate was 74%. This preparation technique requires stringent conditions, and the catalyst used is expensive and hazardous, making industrial application difficult. To save costs and reduce preparation steps, some researchers have used carbon to coat micron-sized porous silicon to form p-Si / G@C composite materials. The resulting silicon-carbon anode material has an initial reversible capacity of 649.4 mA hg. -1 The initial coulombic efficiency (ICE) is 81.85%. This indicates a low initial reversible capacity, uncontrollable particle size, and the need for acid etching, making industrial application difficult. It is evident that most current silicon-carbon material preparation processes use synthetic chemicals as carbon precursors, resulting in high costs, complex processes, and limited industrialization.
[0006] Eutectic solvents (DESs) are mixtures composed of one or more salts or organic compounds, characterized by low melting points and high polarity, and are typically liquid at room temperature. Current techniques for preparing carbon precursors utilize organic solvents, which often require high temperatures to fully dissolve some poorly soluble carbon precursors. In contrast, DESs possess strong dissolving capabilities similar to ionic liquids, effectively dissolving various organic and inorganic compounds, including polymers and inorganic salts, at low temperatures. They also exhibit low toxicity and low volatility, demonstrating excellent safety and environmental friendliness. However, there are no reports on developing a low-temperature, high-efficiency method for dissolving asphalt and etching copper foil current collectors using the mild environment and strong dissolving properties of DESs, thereby enabling the fabrication of asphalt-based high-capacity integrated lithium-ion battery silicon-carbon anodes. Summary of the Invention
[0007] To address the shortcomings and deficiencies of existing technologies, the primary objective of this invention is to provide a method for preparing a high-capacity integrated lithium-ion battery silicon-carbon anode based on asphalt.
[0008] This invention first utilizes the strong solubility and mild reaction environment of eutectic solvents to dissolve asphalt containing a large amount of aromatic ethers and aromatic hydrocarbons. Taking advantage of the amphiphilic properties of these components in the asphalt, strong interfacial forces are generated with silicon, allowing the asphalt to better encapsulate the silicon. Secondly, a surfactant is used to positively charge the nano-silicon powder. The mutual repulsion of positive charges on the silicon surface inhibits silicon powder agglomeration, thus achieving uniform mixing of the positively charged nano-silicon and the negatively charged asphalt, resulting in complete encapsulation of the positively charged nano-silicon by the negatively charged asphalt. Furthermore, due to the high molecular weight of asphalt and its abundance of oxygen-containing functional groups such as hydroxyl and carboxyl groups, it has a very strong affinity for copper foil, allowing the silicon-carbon material to be firmly embedded in the copper foil. Therefore, by directly coating a mixture of nano-silicon and asphalt onto copper foil and vacuum drying, the nano-silicon / asphalt adheres firmly to the copper foil. Following high-temperature calcination, the copper foil is etched and embedded within the foil under high-temperature acidic conditions, simultaneously forming silicon-copper bonds. This yields an asphalt-based, high-capacity, integrated silicon-carbon anode for lithium-ion batteries, which can be directly used as a lithium-ion battery anode. This invention avoids the process of preparing a slurry using silicon-carbon materials, simplifying the silicon-carbon anode preparation process, and also improves the conductivity, specific capacitance, and cycle stability of the silicon-carbon anode.
[0009] This invention utilizes the structural properties of asphalt as a carbon precursor, mixing it with a eutectic solvent to create a carbon precursor solution that etches copper foil. This solution is then mixed with positively charged nano-silicon to produce an embedded layered silicon-carbon anode. This structure significantly accelerates lithium-ion insertion and extraction, substantially improving the energy density, cycle stability, and rate performance of lithium-ion batteries.
[0010] Another advantage of this invention is that the nano-silicon particles can be uniformly coated with asphalt to form a continuous and uniform carbon layer, which solves the problems of severe volume expansion and poor conductivity when silicon is used as a negative electrode material for lithium-ion batteries, and improves the specific capacity, initial coulombic efficiency and rate performance of lithium-ion batteries.
[0011] The objective of this invention is achieved through the following technical solution:
[0012] A method for preparing a pitch-based high-capacity integrated silicon-carbon anode for lithium-ion batteries includes the following steps:
[0013] (1) Dissolve asphalt in a eutectic solvent to obtain an asphalt solution;
[0014] (2) Add nano-silicon powder and surfactant to water, sonicate, filter and dry to obtain positively charged nano-silicon powder;
[0015] (3) Mix and stir the positively charged nano-silicon powder with the asphalt solution to make the nano-silicon powder completely and uniformly dispersed in the asphalt solution to obtain nano-silicon / asphalt mixture.
[0016] (4) The nano-silicon / asphalt mixture is uniformly coated on copper foil with a coating thickness of 50-200μm; after drying, it is calcined at 600-850℃ for 1-5h under a protective atmosphere to obtain the asphalt-based high-capacity integrated lithium-ion battery silicon-carbon anode.
[0017] Preferably, the mass ratio of the nano-silicon powder to the surfactant in step (2) is (1-3):5.
[0018] Preferably, the mass ratio of the positively charged nano-silicon powder to the asphalt in step (3) is (0.5-2):1.
[0019] Preferably, the calcination temperature in step (4) is 700-800℃ and the calcination time is 2-4h.
[0020] Preferably, the eutectic solvent in step (1) is a mixture of choline chloride and hydrogen bond donor in a molar ratio of 1:2; the mass ratio of asphalt to eutectic solvent is 1:(2-6); and the surfactant in step (2) is one or more of hexadecyltrimethylammonium bromide (CTAB), octadecyltrimethylammonium chloride, and N,N-dimethyldodecylamine.
[0021] Preferably, the hydrogen bond donor is one or more of ethylene glycol, glycerol, propylene glycol, sorbitol, and xylitol.
[0022] Preferably, the dissolution conditions in step (1) are: stirring at 20-80℃ for 2-8 hours; the ultrasonic treatment time in step (2) is 20-80 minutes; and the size of the nano-silicon powder is 20-80 nm.
[0023] Preferably, the dissolution conditions in step (1) are: stirring at 20-60℃ for 2-4 hours; and the stirring time in step (3) is 2-10 hours.
[0024] Preferably, the drying in step (4) is to first dry at room temperature for 1-10 hours, and then vacuum dry for 3-24 hours.
[0025] Preferably, the coating thickness in step (4) is 150±30μm, and vacuum drying is performed for 9-24 hours.
[0026] This patent will now be described in more detail.
[0027] In step (1), asphalt has a high viscosity and poor solubility due to its large molecular weight and the presence of a large number of polycyclic aromatic compounds. Therefore, the purpose of this step is to use a eutectic solvent with strong dissolving power to completely dissolve the asphalt at low temperature to form a homogeneous solution, which will help the asphalt to completely and uniformly coat the nano-silicon during the subsequent calcination process.
[0028] In step (2), the size of the nano-silicon powder is 20-80 nm. By modifying the nano-silicon powder with CTAB, positively charged nano-silicon powder is obtained. The electrostatic repulsion of the positive charge on the surface of the nano-silicon powder inhibits the agglomeration of the nano-silicon powder, improves the dispersibility of the nano-silicon powder in the asphalt solution, and thus improves the uniformity of the prepared silicon-carbon material.
[0029] The DES solvent selected in step (3) has good dissolution and dispersion performance for modified nano-silicon. Furthermore, through the interaction between the positive charge on the surface of nano-silicon and the negatively charged asphalt solution, the nano-silicon is uniformly and stably dispersed in the asphalt solution, thereby ensuring that the nano-silicon is completely and uniformly coated by the asphalt during subsequent high-temperature calcination.
[0030] Step (4) requires a suitable coating thickness. The suitable coating thickness is 120-200 μm. When the film is coated on the copper foil surface, the nano-silicon is completely and uniformly coated by the asphalt as the solvent evaporates. Due to the large molecular weight of the asphalt and its rich content of negatively charged groups, it has a strong affinity for the positively charged nano-silicon. In addition, compared with small molecule compounds as carbon sources, the high molecular weight asphalt coating of nano-silicon is more uniform and dense, which can effectively prevent the nano-silicon from being exposed. Furthermore, the asphalt macromolecule contains a large number of hydrophilic functional groups such as hydroxyl and carboxyl groups, and also has a large number of aromatic structures such as benzene rings. Therefore, it has natural amphiphilicity and can be tightly bonded to the nano-silicon powder and copper foil, so that the silicon-carbon material is well embedded on the copper foil surface, reducing the interfacial resistance and improving the electrode stability.
[0031] In step (5), the carbonization temperature is preferably 700-800℃, and the time is 2-4 hours. If the temperature is too low or the time is too short, the carbonization will be incomplete, the asphalt will not etch the copper foil sufficiently, and the silicon-carbon material prepared will have low embedding density and poor stability. If the temperature is too high or the time is too long, the carbon formed by the asphalt will be graphitized to an excessive degree, resulting in a decrease in mechanical stress, which will make it difficult to alleviate the silicon volume expansion during charging and discharging, thus reducing the stability of the electrode material. At the same time, long-term high-temperature carbonization also increases energy consumption and is prone to over-etching and damage to the copper foil used as a current collector.
[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0033] (1) Eutectic solvents are green and efficient solvents with strong dissolving power and a cost far lower than ionic liquids. Using eutectic solvents to dissolve asphalt is more stable and safer than other organic solvents, and can suppress byproducts generated by side reactions. Eutectic solvents also dissolve aromatic ethers and aromatic hydrocarbons in asphalt, allowing them to better coat silica powder.
[0034] (2) In this invention, asphalt and a eutectic solvent are used as etching agents for copper foil. At high temperatures, the asphalt solute etches the copper foil, causing silicon to bond stably to the copper foil. As a carbon precursor, it coats the silicon to form a layered, embedded silicon-carbon composite material. Because asphalt has a high molecular weight and contains abundant oxygen-containing functional groups such as hydroxyl and carboxyl groups, it has a very strong affinity for copper foil, allowing the silicon-carbon material to be firmly embedded in the copper foil. This results in a silicon-carbon composite material with excellent initial charge-discharge capacity.
[0035] (3) The present invention does not have a complicated preparation process. After high-temperature calcination, a high-capacity integrated lithium-ion battery silicon-carbon anode material can be directly obtained without the need for slurry preparation, coating and other steps of the obtained silicon-carbon composite material. Moreover, the lithium-ion battery cell made has excellent electrochemical stability. Attached Figure Description
[0036] Figure 1 This is a rate performance diagram of the integrated lithium-ion battery silicon-carbon anode prepared in Example 1 of the present invention.
[0037] Figure 2 This is the XRD pattern of the integrated lithium-ion battery silicon-carbon anode prepared in Example 1 of the present invention.
[0038] Figure 3 This is a SEM image of the integrated lithium-ion battery silicon-carbon anode prepared in Example 1 of the present invention.
[0039] Figure 4 This is a SEM image comparing the changes in copper foil in the silicon-carbon anode of the integrated lithium-ion battery prepared in Example 1 of this invention.
[0040] Figure 5 This is a graph showing the electrochemical stability of the integrated lithium-ion battery silicon-carbon anode prepared in Example 1 of the present invention.
[0041] Figure 6 This is the XRD pattern of the pitch-based silicon-carbon composite material prepared in Comparative Example 3 of this invention.
[0042] Figure 7 This is a rate performance diagram of the pitch-silicon-carbon composite material prepared in Comparative Example 3 of this invention. Detailed Implementation
[0043] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the implementation of the present invention is not limited thereto.
[0044] Unless otherwise specified in the embodiments of this invention, the conditions shall be performed according to conventional conditions or conditions recommended by the manufacturer. All raw materials and reagents used, unless otherwise specified, are commercially available conventional products.
[0045] Example 1 (Preparation of silicon-carbon anode for pitch-based high-capacity integrated lithium-ion battery)
[0046] 0.2 g of nano-silicon powder (30 nm) was added to 50 ml of an aqueous solution containing 0.5 g of CTAB, sonicated for 30 min, filtered, and dried to obtain positively charged nano-silicon powder. 0.2 g of asphalt was dissolved in 0.8 g of a eutectic solvent (choline chloride: ethylene glycol = 1:2), stirred for 3 h until completely dissolved to obtain an asphalt solution. 0.2 g of positively charged nano-silicon powder was added to the asphalt solution, and stirred for 3 h to obtain a homogeneous asphalt / nano-silicon mixture.
[0047] The obtained asphalt / nano-silicon mixture was uniformly coated onto a copper foil, with a coating thickness of 150 μm. It was then dried at room temperature for 3 hours, followed by vacuum drying for 18 hours to obtain a nano-silicon / asphalt mixture coating with a copper foil substrate. This copper foil substrate nano-silicon / asphalt mixture coating was placed in a tube furnace, purged with inert gas, and calcined at 800°C for 3 hours to carbonize, yielding an asphalt-based high-capacity integrated lithium-ion battery silicon-carbon anode composite material.
[0048] Example 2 (Effect of calcination temperature)
[0049] 0.2 g of nano-silicon powder (30 nm) was added to 50 ml of an aqueous solution containing 0.5 g of CTAB, sonicated for 30 min, filtered, and dried to obtain positively charged nano-silicon powder. 0.2 g of asphalt was dissolved in 0.8 g of a eutectic solvent (choline chloride: ethylene glycol = 1:2), stirred for 3 h until completely dissolved to obtain an asphalt solution. 0.2 g of positively charged nano-silicon powder was added to the asphalt solution, and stirred for 3 h to obtain a homogeneous asphalt / nano-silicon mixture.
[0050] The obtained asphalt / nano-silicon mixture was uniformly coated onto copper foil to a thickness of 150 μm. It was then dried at room temperature for 3 hours, followed by vacuum drying for 18 hours to obtain a nano-silicon / asphalt mixture coating with copper foil as the substrate. This copper foil-based nano-silicon / asphalt mixture coating was then placed in a tube furnace, purged with inert gas, and calcined at 600°C for 3 hours for carbonization. This yielded an asphalt-based high-capacity integrated lithium-ion battery silicon-carbon anode composite material.
[0051] Example 3 (Effect of calcination time)
[0052] 0.2 g of nano-silicon powder (30 nm) was added to 50 ml of an aqueous solution containing 0.5 g of CTAB, sonicated for 30 min, filtered, and dried to obtain positively charged nano-silicon powder. 0.2 g of asphalt was dissolved in 0.8 g of a eutectic solvent (choline chloride: ethylene glycol = 1:2), stirred for 3 h until completely dissolved to obtain an asphalt solution. 0.2 g of positively charged nano-silicon powder was added to the asphalt solution, and stirred for 3 h to obtain a homogeneous asphalt / nano-silicon mixture.
[0053] The obtained asphalt / nano-silicon mixture was uniformly coated onto a copper foil, with a coating thickness of 150 μm. It was then dried at room temperature for 3 hours, followed by vacuum drying for 18 hours to obtain a nano-silicon / asphalt mixture coating with a copper foil substrate. This copper foil substrate nano-silicon / asphalt mixture coating was then placed in a tube furnace, purged with inert gas, and calcined at 800°C for 5 hours for carbonization. This yielded an asphalt-based high-capacity integrated lithium-ion battery silicon-carbon anode composite material.
[0054] Example 4 (Influence of the thickness of the asphalt / nano-silicon composite coating)
[0055] 0.2 g of nano-silicon powder (30 nm) was added to 50 ml of an aqueous solution containing 0.5 g of CTAB, sonicated for 30 min, filtered, and dried to obtain positively charged nano-silicon powder. 0.2 g of asphalt was dissolved in 0.8 g of a eutectic solvent (choline chloride: ethylene glycol = 1:2), stirred for 3 h until completely dissolved to obtain an asphalt solution. 0.2 g of positively charged nano-silicon powder was added to the asphalt solution, and stirred for 3 h to obtain a homogeneous asphalt / nano-silicon mixture.
[0056] The obtained asphalt / nano-silicon mixture was uniformly coated onto a copper foil, with a coating thickness of 200 μm. It was then dried at room temperature for 3 hours, followed by vacuum drying for 18 hours to obtain a nano-silicon / asphalt mixture coating with a copper foil substrate. This copper foil substrate nano-silicon / asphalt mixture coating was then placed in a tube furnace, purged with inert gas, and calcined at 800°C for 3 hours for carbonization. This yielded an asphalt-based high-capacity integrated lithium-ion battery silicon-carbon anode composite material.
[0057] Comparative Example 1 (pure nano-silicon as the negative electrode material)
[0058] 0.2g of 30nm nano-silicon powder was placed in a high-temperature tube furnace, nitrogen gas was introduced, and the temperature was increased to 800℃ at a rate of 5℃ / min, held at that temperature for 2 hours, and then allowed to cool naturally to room temperature. The nano-silicon powder, conductive carbon black, and binder were mixed in a mass ratio of 7:1:2 and ground into a slurry. The slurry was then uniformly coated onto a copper foil and dried in a vacuum drying oven at 80℃ for 12 hours to obtain a silicon anode with a copper foil substrate.
[0059] Comparative Example 2 (using small organic molecules as carbon precursors)
[0060] 0.2 g of nano-silicon powder (30 nm) was added to 50 ml of an aqueous solution containing 0.5 g of CTAB, sonicated for 30 min, filtered, and dried to obtain positively charged nano-silicon powder. 0.2 g of citric acid was dissolved in 0.8 g of a eutectic solvent (choline chloride: ethylene glycol = 1:2), and stirred for 3 h until completely dissolved to obtain a citric acid solution. 0.2 g of positively charged nano-silicon powder was added to the citric acid solution, and stirred for 3 h to obtain a homogeneous citric acid / nano-silicon mixture.
[0061] The obtained citric acid / nano-silicon mixture was uniformly coated onto copper foil to a thickness of 150 μm. It was then dried at room temperature for 3 hours, followed by vacuum drying for 18 hours to obtain a nano-silicon / citric acid mixed coating with copper foil as the substrate. This copper foil-based nano-silicon / citric acid mixed coating was then placed in a tube furnace, purged with inert gas, and calcined at 800°C for 3 hours to carbonize. This yielded a citric acid-based silicon-carbon anode composite material for lithium-ion batteries.
[0062] Comparative Example 3 (Non-integrated silicon-carbon anode)
[0063] Take 0.2g of asphalt, add 0.2g of nano-silica powder (30nm), and stir until a homogeneous nano-silica / asphalt mixture is formed.
[0064] A nano-silicon / asphalt mixture was placed in a high-temperature tube furnace, nitrogen gas was introduced, and the temperature was raised to 800°C at a rate of 5°C / min. The mixture was then calcined at this temperature for 2 hours and allowed to cool naturally to room temperature to obtain a silicon-carbon material. The obtained silicon-carbon material, conductive carbon black, and binder were mixed in a mass ratio of 7:1:2 and ground into a slurry. This slurry was then uniformly coated onto a copper foil and dried in a vacuum drying oven at 80°C for 12 hours to obtain a silicon anode material with a copper foil substrate.
[0065] Comparative Example 4 (Acidic Solvent)
[0066] 0.2 g of nano-silicon powder (30 nm) was added to 50 ml of an aqueous solution containing 0.5 g of CTAB, sonicated for 30 min, filtered, and dried to obtain positively charged nano-silicon powder. 0.2 g of asphalt was dissolved in 0.8 g of sulfuric acid and stirred for 3 h until completely dissolved to obtain an asphalt solution. 0.2 g of positively charged nano-silicon powder was added to the asphalt solution and stirred for 3 h to obtain a homogeneous asphalt / nano-silicon mixture.
[0067] The obtained asphalt / nano-silicon mixture was uniformly coated onto a copper foil, with a coating thickness of 150 μm. It was then dried at room temperature for 3 hours, followed by vacuum drying for 18 hours to obtain a nano-silicon / asphalt mixture coating with a copper foil substrate. This copper foil substrate nano-silicon / asphalt mixture coating was placed in a tube furnace, purged with inert gas, and calcined at 800°C for 3 hours to carbonize. This yielded an asphalt-based lithium-ion battery silicon-carbon anode composite material.
[0068] Comparative Example 5 (Organic Solvent)
[0069] 0.2 g of nano-silicon powder (30 nm) was added to 50 ml of an aqueous solution containing 0.5 g of CTAB, sonicated for 30 min, filtered, and dried to obtain positively charged nano-silicon powder. 0.2 g of asphalt was dissolved in 0.8 g of dimethylformamide and stirred for 3 h until completely dissolved to obtain an asphalt solution. 0.2 g of positively charged nano-silicon powder was added to the asphalt solution and stirred for 3 h to obtain a homogeneous asphalt / nano-silicon mixture.
[0070] The obtained asphalt / nano-silicon mixture was uniformly coated onto a copper foil, with a coating thickness of 150 μm. It was then dried at room temperature for 3 hours, followed by vacuum drying for 18 hours to obtain a nano-silicon / asphalt mixture coating with a copper foil substrate. The resulting nano-silicon / asphalt mixture coating with a copper foil substrate was placed in a tube furnace, purged with inert gas, and calcined at 800°C for 3 hours to carbonize, yielding an asphalt-based silicon-carbon anode composite material for lithium-ion batteries.
[0071] Comparative Example 6 (lignin is a carbon precursor)
[0072] 0.2 g of nano-silicon powder (30 nm) was added to 50 ml of an aqueous solution containing 0.5 g of CTAB, sonicated for 30 min, filtered, and dried to obtain positively charged nano-silicon powder. 0.2 g of lignin was dissolved in 0.8 g of a eutectic solvent (choline chloride: ethylene glycol = 1:2), stirred for 3 h until completely dissolved, to obtain a lignin solution. 0.2 g of positively charged nano-silicon powder was added to the lignin solution, and stirred for 3 h until a homogeneous lignin / nano-silicon mixture was obtained.
[0073] The obtained lignin / nano-silicon mixture was uniformly coated onto copper foil, with a coating thickness of 150 μm. Then, it was dried at room temperature for 3 hours, followed by vacuum drying for 18 hours to obtain a nano-silicon / lignin mixed coating with copper foil as the substrate. The resulting nano-silicon / asphalt mixed coating with copper foil as the substrate was placed in a tube furnace, purged with inert gas, and calcined at 800°C for 3 hours to carbonize, yielding a lignin-based high-capacity integrated lithium-ion battery silicon-carbon anode composite material.
[0074] The battery assembly used a half-cell assembly, model CR2032. The negative electrode material was the same as the copper foil substrate electrode material obtained in the previous example. A lithium sheet was used as the counter electrode. The electrolyte was prepared using 1 mol / L LiPF6 as the solute and ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 1:1:1 as the solvent. The entire assembly process of the lithium-ion half-cell was completed in an argon-protected glove box. Constant current charge / discharge performance tests were conducted using a Neware battery performance testing system at current densities of 100 mA / g and 5 A / g within a voltage range of 0.01 V to 3.0 V. Rate performance tests were conducted at current densities of 100 mA / g, 200 mA / g, 500 mA / g, 1000 mA / g, and 5000 mA / g.
[0075] The different lithium-ion battery anodes prepared in the above examples and comparative examples were applied to lithium-ion batteries, and electrochemical tests and material characterization were performed. The results are shown in Table 1 and... Figure 1-7 .
[0076] Table 1 Comparison of initial capacity and initial coulombic efficiency of different lithium-ion battery anodes
[0077]
[0078]
[0079] Table 1 shows that the integrated lithium-ion battery silicon-carbon anode prepared in Example 1 has a performance of 100 mA·g -1 The initial capacity at the given current density is 2769.35 mAh·g. -1The coulombic efficiency is 88%, and the capacity retention rate after 100 cycles at 1 A / g is 75%. It is evident that the integrated lithium-ion battery silicon-carbon anode prepared in this invention has a high initial capacity and good cycle stability, significantly superior to similar materials. Furthermore, the cycle stability of all sample examples is better than other comparative samples. This is mainly due to the high molecular weight of asphalt and its rich content of oxygen-containing functional groups such as hydroxyl and carboxyl groups, resulting in very strong adhesion to copper foil. Therefore, this invention utilizes a eutectic solvent to effectively dissolve asphalt and nano-silicon, and coats them onto the copper foil current collector. Through a high-temperature environment, the asphalt etches the copper foil, simultaneously generating silicon-copper bonds, thus stably bonding the silicon-carbon anode material to the copper foil. Figure 4 As shown, the asphalt reacts with the copper foil, embedding the material within the copper foil, thereby increasing the material's stability and improving the electrochemical performance of the lithium-ion battery.
[0080] In Comparative Example 1 of Table 1, silicon was used directly as the negative electrode material. During the lithium-ion process, the lack of a carbon precursor as a buffer layer resulted in lower initial efficiency, poor cycle stability, and increased susceptibility to material damage, leading to further capacity reduction. (1 Ag) -1 After 100 cycles, the capacity retention rate dropped sharply to 5%. Comparative Example 2 used commonly synthesized chemicals (small organic molecules) as carbon precursors for silicon-carbon materials. However, because the chemical bonds between these small organic carbon precursors were poor after dissolution, they could not be stably fixed on the copper foil, and even detached after high-temperature calcination. Electrochemical performance tests in lithium-ion batteries showed very poor initial capacity and cycle stability, indicating that this method is not suitable for small organic molecules. Comparative Example 3 used a non-integrated silicon-carbon anode; silicon was oxidized to silicon dioxide by oxygen-containing functional groups in the asphalt. Figure 6 ),Depend on Figure 7 It can be seen that the silicon-carbon material it produces has a strength of 100 mA·g -1 At a current density of only 232.84 mA·g -1 The initial capacity. Comparative Example 4 uses acid to dissolve the asphalt. The acid-dissolved asphalt has no binding properties and will fall off after calcination, resulting in poor battery performance.
[0081] The performance of the lithium-ion batteries assembled in Comparative Examples 4 and 5 in Table 1 shows that the cycle stability of both batteries is worse than that of Example 1. This indicates that using other solvents to dissolve asphalt cannot achieve the effect of dissolving asphalt with eutectic solvents. The uniformity of carbon-coated nano-silicon is poor, resulting in poor battery cycle stability.
[0082] The performance of lithium-ion batteries assembled in Comparative Example 6 in Table 1 shows that asphalt, as a carbon precursor, exhibits more stable battery cycle stability compared to lignin-based silicon-carbon composites.
[0083] Figure 1This is a rate performance diagram of the integrated lithium-ion battery silicon-carbon anode prepared in Example 1 of the present invention. Under different current densities, the specific capacity of the integrated lithium-ion battery silicon-carbon anode can reach a stable state after several cycles, and the specific capacity starts from 100 mA·g. -1 Transformed to 5000mA·g -1 The fact that it can still stabilize quickly indicates that the asphalt-based high-capacity integrated lithium-ion battery silicon-carbon anode has excellent rate performance and cycle stability, and can operate stably under different working environments.
[0084] Figure 2 This is the XRD pattern of the integrated lithium-ion battery silicon-carbon anode prepared in Example 1 of the present invention. The prepared integrated lithium-ion battery silicon-carbon anode material is mainly composed of amorphous carbon and elemental silicon.
[0085] Figure 3 This is a SEM image of the silicon-carbon anode material prepared in Example 1 of this invention. The image shows that the particle size of the integrated lithium-ion battery silicon-carbon anode material is approximately 40–80 nm, and the nano-silicon particles are uniformly coated with a continuous layer of pitch carbon.
[0086] Figure 4 These are comparative SEM images showing the morphological changes of the copper foil before and after the preparation of the integrated lithium-ion battery silicon-carbon anode material obtained in Example 1 of this invention. Image a shows the original copper foil, with a tight surface and no cracks. Image b shows the copper foil after the surface silicon-carbon material of the integrated lithium-ion battery silicon-carbon anode material prepared in Example 1 has been scraped off; obvious indentations and cracks are visible, indicating that the asphalt reacted with the copper, embedding the material within the copper foil. This is a key factor in increasing the conductivity and cycle stability of the anode material.
[0087] Figure 5 This is an electrochemical stability diagram of the integrated lithium-ion battery silicon-carbon anode material prepared in Example 1 of this invention. It can be seen that this electrode has a high initial capacity and excellent cycle stability.
[0088] Figure 6 This is the XRD pattern of the pitch-based silicon-carbon composite material prepared in Comparative Example 3 of this invention. It can be seen that pitch oxidizes the nano-silicon powder into silicon dioxide. In addition, in this comparative example, the prepared silicon-carbon composite material powder was mixed with other electrode additives, coated onto copper foil, and then a battery was installed to measure its performance. There are no chemical bonds between the silicon-carbon composite material and the copper foil, resulting in poor electrode stability.
[0089] Figure 7 This is a rate performance graph of the pitch-based silicon-carbon composite material prepared in Comparative Example 3 of this invention. As can be seen from the rate performance graph, after the silicon in Comparative Example 3 is oxidized to silicon dioxide, the lithium-ion battery prepared from it achieves a rate performance of 100 mA·g⁻¹. -1 The initial reversible capacity at the given current density is only 232.84 mAh·g. -1 .
[0090] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for preparing a pitch-based silicon-carbon anode material for lithium-ion batteries, characterized in that, Includes the following steps: (1) Dissolve asphalt in a eutectic solvent to obtain an asphalt solution; the eutectic solvent is a mixture of choline chloride and a hydrogen bond donor in a molar ratio of 1:2; the hydrogen bond donor is one or more of ethylene glycol, glycerol, propylene glycol, sorbitol, and xylitol. (2) Add nano-silicon powder and surfactant to water, sonicate, filter and dry to obtain positively charged nano-silicon powder; (3) Mix and stir the positively charged nano-silicon powder with the asphalt solution to make the nano-silicon powder completely and uniformly dispersed in the asphalt solution to obtain nano-silicon / asphalt mixture. (4) The nano-silicon / asphalt mixture is uniformly coated on the copper foil, and the coating thickness is 50-200μm; After drying, the asphalt-based silicon-carbon anode material for lithium-ion batteries is obtained by high-temperature calcination at 600-850℃ for 1-5 hours under a protective atmosphere.
2. The preparation method according to claim 1, characterized in that, In step (2), the mass ratio of nano-silicon powder to surfactant is (1~3):5; in step (3), the mass ratio of positively charged nano-silicon powder to asphalt is (0.5~2):
1.
3. The preparation method according to claim 1, characterized in that, The calcination temperature in step (4) is 700-800℃ and the calcination time is 2-4h.
4. The preparation method according to any one of claims 1 to 3, characterized in that, The surfactant in step (2) is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride and N,N-dimethyldodecylamine.
5. The preparation method according to claim 4, characterized in that, The mass ratio of asphalt to eutectic solvent in step (1) is 1:(2-6).
6. The preparation method according to any one of claims 1 to 3, characterized in that, The dissolution conditions in step (1) are: stirring at 20-80℃ for 2-8 hours; the ultrasonic treatment time in step (2) is 20-80 minutes; and the size of the nano-silicon powder is 20-80 nm.
7. The preparation method according to claim 6, characterized in that, The dissolution conditions in step (1) are: stirring at 20-60℃ for 2-4 hours; the stirring time in step (3) is 2-10 hours; the drying in step (4) is: first drying at room temperature for 1-10 hours, and then drying under vacuum for 3-24 hours.
8. The preparation method according to claim 7, characterized in that, The coating thickness in step (4) is 150±30μm, and it is vacuum dried for 9-24h.
9. The asphalt-based lithium-ion battery silicon-carbon anode material prepared by the method according to any one of claims 1 to 8.
10. The application of the pitch-based lithium-ion battery silicon-carbon anode material according to claim 9 in the preparation of lithium-ion batteries.